Wind farm location determination by using a two-phased fuzzy decision-making methodology based on fused data with a real case application - Karasan, Ali; Colak, Murat; Budak, Aysenur; Kaya, Ihsan (TAYLOR & FRANCIS LTD, 2022)
Location selection for power plants operating with renewable energy is critical, and their locations directly affect performance and productivity. In this paper, a novel two-phased MCDM methodology based on z-fuzzy numbers with a better modelling capability by defining a confidence degree in decision-making problems is proposed to evaluate alternative locations for wind farm installation in Marmara Region, Turkey. As a result, while Canakkale has been selected as the most suitable city, the alternative location named Biga has been determined as the most appropriate location in this city for wind farm installation. In addition, sensitivity and comparative analyses have been conducted to check the flexibility of the given decisions and verification of the weights of the criteria, respectively.
Keywords: Wind energy; location selection; fuzzy set theory; MCDM; AHP; TOPSIS; Z-fuzzy numbers; Marmara Region; ANALYTIC HIERARCHY PROCESS; MULTICRITERIA ANALYSIS; GIS; MODEL; Science & Technology - Other Topics; Energy & Fuels